Noticias falsas, desinformación y alfabetización mediática en Iberoamérica: un debate necesario - Romero-Rodriguez, Luis M. (2025)
Disinformation has become a critical problem in contemporary societies, threatening democratic processes, public health, and social cohesion. In Ibero-America, the spread of fake news and deceptive content has gained prominence over the past decade, driven by the massive penetration of social networks and messaging apps. This article presents a review of scientific literature on fake news and disinformation in the Ibero-American context, with emphasis on the fundamental role of media, information, and digital literacy for future generations. It addresses the concepts of fake news and disinformation, their documented social impacts, and the responses developed by academia and public policy. The review highlights how media and information literacy is emerging as a key strategy —complementing legal and technological measures— to strengthen critical thinking and citizen resilience against disinformation. Likewise, it explores media education initiatives in Ibero-America, including educational programs, fact-checking projects, and recent public policies, revealing achievements and challenges. The literature suggests that integrating media literacy throughout formal education is essential to forge critical and engaged digital citizens. Finally, future perspectives in the fight against disinformation are discussed, underscoring the importance of multisector collaboration involving governments, media, digital platforms, educational institutions, and civil society in building a more truthful and inclusive information culture.